Analysis of metallic antennas and scatterers - Popovic, Branko D.; Kolundzzija, Branko M. (Institution of Electrical Engineers, 1994)
Most antennas are assembled from conducting surfaces and wires. The usual approach to numerical analysis of such structures is to approximate them by small surface or wire elements, with simple current approximation over the elements (the so-called subdomain approach), which requires a large amount of computer storage. This book describes a novel general entire-domain method for the analysis of metallic antennas and scatterers which enables the solution of a very wide class of problems to be obtained using computers of relatively modest capability. Antenna-design engineers, scientists and graduate students interested in the analysis and design of electrically small and medium-sized metallic antennas and scatterers will find in this book a self-contained and extremely powerful tool that circumvents most difficulties encountered in other available methods.